Studying the Effect of Radomes on Microstrip Patch Antennas Using Defferent Dielectric Substrate Constants - V.Saidulu (International Journal of Advanced Science and Technology, 2020)
Microstrip patch antennas are find wide applications in high speed vehicles, missiles, tanks and satellite communications. In these applications radome (or dielectric cover) is required for protections from environmental effects. The main advantages of these antennas over conventional microwave antenna are light weight, low volume, low profile, low cost, planar structure and easy compatibility with integrated circuits. The present paper deals with empirical studying the effect of radome (or dielectric cover) on rectangular, circular and square patch microstrip antennas and also comparing their performance characteristics such as resonant frequency, gain, bandwidth, beam width, return loss and VSWR using different dielectric constant of radomes substrates. The proposed model of rectangular, circular and square patch microstrip antennas were designed at centre frequency of 2.4 GHz which is lying in S –band region and fabricated on Arlon diclad substrate, having the dielectric constant 2.2 and the thickness is 1.6mm. Different dielectric constant of radomes substrates such as Arlon AD 880, Arlon AD 320, FR4 and Arlon AD1000 are used for empirical studying on microstip patch antennas. These microstrip patch antennas are used in linear polarization applications.